The Evaluation, Production, and Derivatisation of the Garcinia Acid in Garcinia Atroviridis - Zainal Abidin, Habibah (2005)
A method for extraction and isolation of garcinia acid from Garcinia atroviridis (G.atr0viridi.s) was developed. Using this method high yields of garcinia acid in the range of 90-95 g from 500 g of the dried rinds were accomplished. This method is low cost and simple. The garcinia acid isolated from this procedure was converted to its calcium salt of HCA lactone to ensure that the compound was stable and less hygroscopic. From the analysis using high performance liquid chromatography (HPLC), three peaks of organic acids were observed and identified as a-hydroxycitric acid lactone (HCA lactone), a-hydroxycitric acid (HCA) and citric acid based on spiking with standard acids and retention time. The amount of the HCA was 72 % wlw, the HCA lactone was 17 % wlw and the citric acid was 0.4 % wlw in the calcium salt of HCA lactone. The calcium salt of HCA lactone was derivatised into ester. The esterification products are dimethyl tetrahydro-3-hydroxy-5-oxo-2,3-furandicarboxylate and diethyl tetrahydro-3-hydroxy-5-oxo-2,3-furandicarboxylateB. oth esters were tested for biological activity towards nitric oxide (NO). Unfortunately, both compounds were found inactive towards NO inhibition RAW 264.7 cell treated with lipopolysaccharide (LPS) and interferon-y (IFN-y).